2004
DOI: 10.1038/sj.ejcn.1602064
|View full text |Cite
|
Sign up to set email alerts
|

Validity of reported energy expenditure and reported intake of energy, protein, sodium and potassium in rheumatoid arthritis patients in a dietary intervention study

Abstract: Objectives: The aim of the study was to validate a diet history interview (DHI) method and a 3-day activity registration (AR) with biological markers. Subjects and study design: The reported dietary intake of 33 rheumatoid arthritis patients (17 patients on a Mediterraneantype diet and 16 patients on a control diet) participating in a dietary intervention study was assessed using the DHI method. The total energy expenditure (TEE), estimated by a 3-day AR, was used to validate the energy intake (EI). For nine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…This was in line with Hagfors et al (2005) who did not find a difference between salt intake, determined from a dietary history interview and 24-h urine samples, whereas Reinivuo et al (2006) found a lower intake of salt, determined from a 48-h dietary recall rather than from 24-h urine samples, in women but not in men. Total salt intake determined from 24-h urinary excretion of sodium in the present study was close to the values found in Holland (10.1 and 7.7 g salt per day for men and women, respectively) and slightly higher than results from Germany (9.7 and 6.7 g salt per day in men and women, respectively) (Joossens et al, 1996).…”
Section: Discussionsupporting
confidence: 70%
“…This was in line with Hagfors et al (2005) who did not find a difference between salt intake, determined from a dietary history interview and 24-h urine samples, whereas Reinivuo et al (2006) found a lower intake of salt, determined from a 48-h dietary recall rather than from 24-h urine samples, in women but not in men. Total salt intake determined from 24-h urinary excretion of sodium in the present study was close to the values found in Holland (10.1 and 7.7 g salt per day for men and women, respectively) and slightly higher than results from Germany (9.7 and 6.7 g salt per day in men and women, respectively) (Joossens et al, 1996).…”
Section: Discussionsupporting
confidence: 70%
“…Four of the studies 10,43,47,48 in the review used objective measurement tools while the remaining 12 used only subjective outcome measures. The use of differing measurement tools leads to greatly differing output styles also.…”
Section: Resultsmentioning
confidence: 99%
“…The use of differing measurement tools leads to greatly differing output styles also. They include kJ/day, 10 hrs/week, 49 hrs/day, 42 mins/ day, 42,49 MJ/day, 47 kcals/week, 41 mins/week, 45,50 kcals/ day, 48 METmin per week 51 and METhours/day, 52 as well as exercise level, 38 physical activity level, 47 sum score of outcome measure, 44,46 meeting of national recommendations, 50 daily average number of steps, 48 number of steps taken, 43 vigor of steps, 43 time spent standing, 43 total energy in arbitrary units, 43 participation in activity domains, 39 and % in different physical activity categories. 40 …”
Section: Resultsmentioning
confidence: 99%
“…An average intake for the 3 reported days before the follow-up assessment was calculated for each nutrient. Because dietary self-reporting is prone to error, [43][44][45][46] a margin of 10% below the recommendations and Recommended Dietary Allowances (RDAs) was used to define suboptimal intake.…”
Section: Intakementioning
confidence: 99%